2012
DOI: 10.1080/19425120.2012.675975
|View full text |Cite
|
Sign up to set email alerts
|

Passage of American Shad: Paradigms and Realities

Abstract: Despite more than 250 years of development, the passage of American shad Alosa sapidissima at dams and other barriers frequently remains problematic. Few improvements in design based on knowledge of the swimming, schooling, and migratory behaviors of American shad have been incorporated into passage structures. Large-scale technical fishways designed for the passage of adult salmonids on the Columbia River have been presumed to have good performance for American shad but have never been rigorously evaluated fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 31 publications
3
31
0
Order By: Relevance
“…Detection records showed tagged American Shad (including ones at LD‐1) being suddenly undetected in the array, indicating that they potentially succumbed to starvation, predation, or harvest. Immediately downstream of LD‐1, many acoustic‐tagged American Shad experienced delays (e.g., only 33% passed within a week), and we observed numerous individuals in eddies to the side of the main fishway flow during electrofishing, something also observed by Haro and Castro‐Santos (). Simulation modeling suggested that migratory delays (especially downstream) are more detrimental than reduced passage for American Shad populations along the northeast Atlantic coast, as mortality reduces repeat spawners in iteroparous populations (Castro‐Santos and Letcher ; Stich et al.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Detection records showed tagged American Shad (including ones at LD‐1) being suddenly undetected in the array, indicating that they potentially succumbed to starvation, predation, or harvest. Immediately downstream of LD‐1, many acoustic‐tagged American Shad experienced delays (e.g., only 33% passed within a week), and we observed numerous individuals in eddies to the side of the main fishway flow during electrofishing, something also observed by Haro and Castro‐Santos (). Simulation modeling suggested that migratory delays (especially downstream) are more detrimental than reduced passage for American Shad populations along the northeast Atlantic coast, as mortality reduces repeat spawners in iteroparous populations (Castro‐Santos and Letcher ; Stich et al.…”
Section: Discussionsupporting
confidence: 84%
“…At the spillway along the partially removed dam in the Little River, North Carolina, American Shad passage increased with water depth; depth had no relationship with Flathead Catfish passage (Raabe and Hightower ). American Shad (evening peak) and Striped Bass (morning peak) both appeared to prefer traversing the fishway with light, similar to behavior observed at other fishways (Haro and Castro‐Santos ), possibly due to their being able to see while navigating through the structure. Conversely, Flathead Catfish primarily completed passage during nocturnal hours, when they typically are more active (Vokoun and Rabeni ).…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…This behaviour suggested that Alewife seem to avoid strong horizontal vortices, perhaps related to the fact that they are an ocean-dwelling, schooling species that is not particularly adapted to bed-generated turbulent flow. Avoidance and disorientation in highly turbulent flow has also been observed for other clupeids such American shad (Larinier and Travade 2002;Haro and Castro-Santos 2012). In contrast, Brook Trout frequently sought shelter behind both horizontal and vertical baffles and therefore reached higher D max particularly in repeated attempts.…”
Section: Discussionmentioning
confidence: 55%
“…The construction of fishways at dams is one approach used to mitigate obstructions to migrating fish. However, many of the fishways in rivers along the east coast of the United States have not been thoroughly evaluated for passage of American Shad and often adopted designs intended to be suitable for Pacific Salmon (Haro and Castro‐Santos ). Quantifying fish behavior under the variability of altered environmental conditions (e.g., flows) imposed by dams may inform managers of the efficacy of fish passage structures and identify areas for modification.…”
mentioning
confidence: 99%